Controllable growth of SnS2 nanostructures on nanocarbon surfaces for lithium-ion and sodium-ion storage with high rate capability. Issue 4 (11th January 2018) - Luo, Bin; Hu, Yuxiang; Zhu, Xiaobo; Qiu, Tengfei; Zhi, Linjie; Xiao, Mu; Zhang, Haijiao; Zou, Mingchu; Cao, Anyuan; Wang, Lianzhou
Abstract : Structural evolution of SnS2 from vertically or parallelly aligned nanosheets to ultra-small nanocrystals on nanocarbon surfaces is demonstrated and the latter exhibit enhanced rate performance and cycling stability for both Li-ion and Na-ion storage. Abstract : Two-dimensional (2D) layered metal dichalcogenides (LMDs) with semiconducting character have been attracting increasing attention in both fundamental studies and various applications. In the case of electrode material design for energy storage, integrating metal dichalcogenides with other conductive phases such as nanocarbons has been widely recognised as an efficient way to simultaneously achieve good electrochemical activity and conductivity. However, controllable growth of metal dichalcogenides on nanocarbons with well-defined structure and efficient interfacial contact is still highly challenging. In this work, we report a new class of SnS2 nanosheets with distinct growth orientations on the surfaces of reduced graphene oxide (RGO) and carbon nanotubes (CNTs). We further demonstrate a spatial confinement strategy to in situ grow SnS2 nanoparticles, which are homogeneously confined within RGO or CNT based porous carbon matrices. Consequently, these resultant 3D architectures demonstrate outstanding rate capability and cycling stability due to their synergistic effect of electrochemically active SnS2 particles and highly conductive carbon matrixes. In particular, the free-standing CNT sponge based composite delivers specific capacities of 741 and 462 mA h g −1 at 3200 mA g −1 for Li + and Na + storage, respectively, among the best values reported for both lithium ion battery (LIB) and sodium ion battery (NIB) systems. This work not only provides better understanding of the growth mechanisms of metal dichalcogenides on nanocarbons but also opens a new way to construct unique 2D heterostructures for various applications.